(untitled) (The International Research Journal of Management Science, 2017)
The major objective of the study is to know the determinant of bank selection among working people in Kathmandu Valley. The study has explored seven factors which are core service delivery, external and internal aesthetics of bank, convenience, financial benefit, technology, recommendation by peers and staff. The study developed the questionnaire considering these seven factors and to confirm the reliability, questionnaire was distributed to 10 people which revealed questionnaire was fairly reliable for research administration. Arithmetic Mean, ANOVA and correlation analysis are basis for statistical analysis. The study finds that convenience significantly impacts the banking decisions among working people in Kathmandu Valley which includes item like convenient location, close to home, adequate number of location, security, convenience, reputation of organization and proximity. Bank should focus more on items like accurate account information and pleasant bank atmosphere. Working people are more sensitive in cost rather than benefit and they are more sensitive to interest rate in fixed deposit to saving in banking decision. Correlation analysis in study asserts that recommendation by peers is weekly correlated with other factor which research found that banks need to improve in faster service, queue management, front desk employee, ATM and mobile service and information sharing.